Forced vibration analysis of milling machine's hexapod table under machining forces - Pedrammehr, Siamak (Strojniški vestnik, 2014)
Assuming a sinusoidal machining force, the forced vibration of a machine tools' hexapod table in different directions is addressed in the present study. A vibration model for the hexapod table is developed and the relevant explicit equations are derived. In the vibration equation of the table, the pods are assumed as spring-damper systems and the equivalent stiffness and damping of the pods are evaluated using experimental results obtained by modal testing on one pod of the hexapod table. The results of the analytical approach have been verified by FEM simulation. The theoretical and FEM results exhibit similar trends in changes and are close to each other. The vibration of the table in different positions has been studied for rough and finish machining forces for both down and up milling. The ranges of resonance frequencies and vibration amplitudes have also been investigated. The safe functional modes of the table in terms of its upper platform's position have subsequently been determined.
Keywords: modalne analize; obdelovalni stroji; paralelna kinematika; rezalne sile; šesteronožni mehanizmi